Guaranteed Cost Finite-Time Control for Positive Switched Linear Systems with Time-Varying Delays - Xiangyang Cao; Leipo Liu; Zhumu Fu; Xiaona Song; Shuzhong Song (Journal of Control Science and Engineering)
This paper considers the guaranteed cost finite-time control for positive switched linear systems with time-varying delays. The definition of guaranteed cost finite-time boundedness is firstly given. Then, by using the mode-dependent average dwell time approach, a static output feedback law and a state feedback control law are constructed, respectively, and sufficient conditions are obtained to guarantee that the closed-loop system is guaranteed cost finite-time boundedness. Such conditions can be easily solved by linear programming. Finally, an example is given to illustrate the effectiveness of the proposed method.